The expression level of microRNA-122 in patients with type 2 diabetes mellitus in correlation with risk and severity of coronary artery disease - Nearmeen M Rashad; Tamer M Ezzat; Reem M Allam; Mohamad H Soliman; Mohammed S Yousef (SpringerOpen, 2019)
Background Type 2 diabetes mellitus (T2DM) has reached epidemic proportions worldwide. Coronary artery disease (CAD) is one of the most important causes of mortality worldwide. MicroRNAs (miRNAs) modulate gene expression and is involved in the pathogenesis of T2DM and CAD. The objective of the current study was to explore the expression pattern of miR-122 in T2DM with or without CAD. Moreover, we aimed to evaluate the association between miR-122 and risk and severity of CAD in T2DM. Participants and methods This cross-sectional controlled study enrolled 130 patients with T2DM and 110 control group. The enrolled diabetic patients were classified into two groups: seventy patients without CAD and 60 patients without CAD. All patients were investigated using a 12-lead standard ECG, echocardiography, and coronary arteriography. The serum MiR-122 expression profile was measured using quantitative real-time (qRT) PCR. Results miRNA-122 expression levels were significantly higher in T2DM, in particular patients with T2DM with CAD, compared with the control group. Interestingly, miRNA-122 expression levels were positively correlated with cardiometabolic risks and severity of coronary occlusion. Linear regression analysis test showed that miRNA-122 were independently correlated with high-density lipoprotein, ejection fraction, and uric acid. The power of miRNA-122 expression level to diagnose T2DM among studied participants was evaluated using receiver operating characteristic. The area under curve was 0.997 (95% confidence interval=0.993-1.00), with sensitivity of 96.9% and specificity of 99%, and regarding the power for differentiating patients with T2DM with CAD from patients with T2DM without CAD, the area under curve was 0.832 (95% confidence interval=0.763-0.902), with sensitivity of 93.3% and specificity of 96.86%. Conclusion The miRNA-122 expression levels were higher in the T2DM group compared with controls, in particular patients with CAD. The higher levels of miR-122 expression were strongly correlated with cardiometabolic risk factors and severity of coronary occlusion. Therefore, miR-122 expression levels seem to be a noninvasive biomarker for CAD.